PRESSURE ANALYSIS AND FLUID CONTACT PREDICTION FOR ALPHA RESERVOIR (A PARTIALLY APPRAISED FIELD) ONSHORE NIGER DELTA. (Nigerian Journal of Technology, 2017)
The study field is green, with limited well penetrations. The objective reservoir (Alpha Reservoir) is a relatively shallow one, with 6 wells penetration. Two of the wells are wet (Water-Up-To) while the rest penetrated hydrocarbon bearing intervals (Gas-Down-To). As pressure data was not acquired in the water leg of the reservoir, pressure gradient analysis was done with the field-wide hydrostatic profile for contact and fluid prediction. Also, an evaluation of the possibility of having an oil rim within the region of fluid-type uncertainty was carried out. The predicted results revealed that the objective reservoir has the potential of having oil rim of a possible gradient 0.20psi/ft., with a column height of less than or equal to 20ft. Such an oil column if present is deemed insignificant. Therefore, the reservoir can be developed as a non- associated gas reservoir with a predicted Gas-Water-Contact of 7529ftss. http://dx.doi.org/10.4314/njt.v36i3.20